Peningkatan keterampilan keelektronikaan untuk meningkatkan daya saing dan kemandirian siswa SMK menghadapi persaingan global - Ridwansyah Ridwansyah (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This training activity aims to have students gain practical electronic skills as a first step to improve student competence in facing global competition. This training focuses on issues of repair and maintenance of household electronic equipment. This training activity is carried out using the Problem Based Learning (PBL) learning model, which is carried out using lecture and demonstration methods as well as practice. At the end of the activity, an evaluation of the material was carried out. The evaluation was carried out in the form of repairing damaged household electronic equipment. This training activity took place properly according to the results of the questionnaire given to participants. the results of the questionnaire namely: assessment of participants related to the training material provided (score 4.33), increased technical ability (score 4.00), the emergence of an entrepreneurial spirit (score 4.13), increased confidence to open a business (score 4.00) and increased competitiveness face global competition (score 4.27).